The last titan : a life of Theodore Dreiser - Loving, Jerome, 1941- (University of California Press, 2005)
When Theodore Dreiser first published Sister Carrie in 1900 it was suppressed for its seamy plot, colloquial language, and immorality - for, as one reviewer put it, its depiction of "the godless side of American life." It was a side of life experienced firsthand by Dreiser; whose own circumstances often paralleled those of his characters in the turbulent, turn-of-the-century era of immigrants, black lynchings, ruthless industrialists, violent labor movements, and the New Woman. This masterful critical biography, the first on Dreiser in more than half a century, is the only study to fully weave.